Effects of Norms, Place Attachment, Environmental Concerns, and Altruism on Environment-friendly Tourism Behavior - Yildirim, Hacı Mehmet; Soylu, Yasin; Atay, Lütfi (Journal of Tourism, Sustainability and Well-being, 2024)
This study investigates the impact of the subjective and personal norms, environmental concerns, and altruism perceptions of recreationists on environment-friendly behaviors and environmental tourism behaviors. The population of the study consists of recreationists visiting the Ida Mountains in the western coast of Turkey. Visitors taking hiking trails as a recreational activity were included in the study and 221 complete responses were received. Partial Least Square Structural Equation Model (PLS-SEM) was applied to test research hypotheses. The findings show that (a) subjective norms, place attachment, environmental concern, and environmental altruism positively influence environment friendly behavior; (b) personal norms are non-significant antecedents of environment friendly behavior; and (c) environment friendly behavior is a significant antecedent of environmental tourism behavior. This shows that recreationists in Ida Mountains are more sensitive as they partake in tourism-related activities and pay attention to their attitudes and behaviors towards environmental problems when they interact with the environment. Revealing the effects of norms, place attachment, environmental concerns and altruism on environmentally friendly tourism behavior can support the development of sustainable tourism policies and programs. In this way, it can provide sustainability-related information to stakeholders in the tourism industry, policy makers and destination managers.